Synthesis of Layered Double Hydroxidenanocomposites Using N-(2-Hydroxyethyl)-Ethylenediamine Triacetatic Acid and Anthraquinone-2-Sulphonic Acid as Guest Anions - Musa, Mazlina (2005)
The synthesis of a new nanocomposite material consisting of inorganic layers, MgIAl- NO3' (MAL) and CoIAI-NO< (COAL) as hosts and N-(2-hydroxyethy1)-ethylenediamine triacetate (HEDTA), an guest anion was successfully done by using conventional method. The PXRD results showed that the intercalation of HEDTA anion into the MgIAI-N03- and CoIAl-NOYwith Mg/Al and CoIAl ratio of 5 were readily accomplished, resulting in the formation of nanocomposite materials, Mg/AI-HEDTA (MATAS) and CoIAl- HEDTA (COATAS), with the expansion of the interlayer spacing from 8.0 A to 14.8 A and 8.9 A to 15.3 A, respectively. This expansion is to accommodate the HEDTA anion of a larger size than nitrate. FTIR spectra of MATAS and COATAS showed a combination pattern of HEDTA with MALS and COALS, respectively. The elemental analysis showed the presence of Mg, Al, C and Co in the surface of the synthesized materials. Thermal analysis showed that the MALS and COAL5 gradually collapsed starting at around 600 O C . Scanning electron microscopy (SEM) study showed no significant difference between the surface morphology of MAL5, COALS, MATAS and COATA5. Anion exchange of anthraquinone-2-sulphonate (AQ2) with nitrate from the Zn-A1 layered double hydroxide (ZAL) was accomplished in aqueous environment at various concentrations, temperatures and contact times. The anion exchange procedure produced nanocomposite materials, of which basal spacing was expanded from 9.2 to around 20 A. This is due to the size and spatial orientation of the anions, which is accommodated in the ZAL inorganic layered structure. Relatively pure phase products were obtained as a result of complete anion exchange process when the concentration of aqueous solutions of AQ2 of 0.01-0.025 M, contact time of 18 h and temperature of 70 "C (ZALAQ2S) were used. However, a relatively impure phase was obtained at lower temperatures, 25- 50 O C when 0.025 M AQ2 was used in the anion exchange process for 18 h of contact time. At 0.025 M AQ2, anion exchange process could be observed at room temperature even only afier 10 min contact time, but the resulting materials did not afford pure phase even after 48 h. The anion-exchang rate for AQ2 with nitrate was found to be very fast for the first 200 min, followed by a slow process thereafter and finally becomes almost leveled off after 1000 min. FTIR spectrum of ZALAQ2S showed a combined pattern of both the FTIR spectra of ZAL and AQ2. The elemental analyses showed that the presence of Zn, A1 and C in the surface of the as-synthesized ZALAQ2S and ZAL. SEM analysis shows that the surface morphology of ZAL at 5000 x magnifications is more compact than ZALAQ2S.